2020
DOI: 10.3390/nu12020308
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Grateloupia elliptica, a Red Seaweed, in Mice with High-Fat Diet-Induced Obesity via Suppression of Adipogenic Factors in White Adipose Tissue and Increased Thermogenic Factors in Brown Adipose Tissue

Abstract: Obesity is a serious metabolic syndrome characterized by high levels of cholesterol, lipids in the blood, and intracellular fat accumulation in adipose tissues. It is known that the suppression of adipogenic protein expression is an effective approach for the treatment of obesity, and regulates fatty acid storage and transportation in adipose tissues. The 60% ethanol extract of Grateloupia elliptica (GEE), a red seaweed from Jeju Island in Korea, was shown to exert anti-adipogenic activity in 3T3-L1 cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…The ethanolic extract of Grateloupia elliptica (60%) reduced the accumulation of the lipid in 3T3-L1 cells and inhibited the adipogenic proteins expression. In addition to a significant decreasing in body weight of C57 BL/6J male mice, as well as reducing white adipose tissue (WAT) weight, e.g., fatty liver, leptin, total cholesterol, and serum triglycerides contents in vivo without cytotoxic effect [ 79 ]. Forty % of Plocamium telfairiae ethanolic extract showed anti-obesity ability via reducing the fat accumulation and suppressed the expression of major adipogenesis factors, like peroxisome proliferator-activated receptor-γ (PPAR-γ),CCAAT/enhancer-binding protein (C/EBP)-α, sterol regulatory element-binding protein 1 (SREBP-1), and phosphorylated ACC (pACC) in 3T3-L1 cells [ 80 ].…”
Section: Anti-obesity Activitymentioning
confidence: 99%
“…The ethanolic extract of Grateloupia elliptica (60%) reduced the accumulation of the lipid in 3T3-L1 cells and inhibited the adipogenic proteins expression. In addition to a significant decreasing in body weight of C57 BL/6J male mice, as well as reducing white adipose tissue (WAT) weight, e.g., fatty liver, leptin, total cholesterol, and serum triglycerides contents in vivo without cytotoxic effect [ 79 ]. Forty % of Plocamium telfairiae ethanolic extract showed anti-obesity ability via reducing the fat accumulation and suppressed the expression of major adipogenesis factors, like peroxisome proliferator-activated receptor-γ (PPAR-γ),CCAAT/enhancer-binding protein (C/EBP)-α, sterol regulatory element-binding protein 1 (SREBP-1), and phosphorylated ACC (pACC) in 3T3-L1 cells [ 80 ].…”
Section: Anti-obesity Activitymentioning
confidence: 99%
“…Dietary studies in Japan and South Korea showed that consumption of seaweed can reduce the incidence of chronic diseases such as cancer, hyperlipidemia and coronary heart disease [ 16 , 17 ]. The existing evidence shows that algae, especially spirulina, has antioxidant, anti-inflammatory, antitumor, antiviral, antibacterial and other health-promoting functions, and has a positive therapeutic effect on hyperlipidemia, obesity, cardiac vascular disease (CVD) and diabetes [ 15 , 18 , 19 , 20 , 21 ]. Polyphenols extracted from seaweed are thought to contribute to reducing the risk of cardiovascular disease and diabetes complications due to hyperglycemia, hyperlipidemia, oxidative damage and chronic inflammation, as well as metabolic abnormalities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [17] analyzed the effects of a 60% ethanol extract of Grateloupia elliptica (GEE), a red seaweed from Jeju Island in Korea, on lipid accumulation and adipogenesis in 3T3-L1 adipocytes. Cells were treated during adipocyte differentiation (8 days) with 25, 50, 100 or 200 µg/mL of the seaweed extract.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Lee et al [17] studied the anti-obesity effects of the 60% ethanol extract of the red seaweed Grateloupia elliptica in mice fed a high-fat diet. For this purpose, 5-6-week-old male C57 BL/6J mice were divided into four experimental groups: the CD group was fed a chow diet, the HFD group was fed a high-fat diet, the L-GEE group was fed the same high-fat diet supplemented with a low dose of G. elliptica (125 mg/kg body weight/day), and the H-GEE group was fed the same high-fat diet supplemented with a high dose of G. elliptica (250 mg/kg body weight/day).…”
Section: Red Seaweedmentioning
confidence: 99%